Psychopathological Factors and Perpetration of Intimate Partner Aggression: A Multivariate Model - Jose, Anita (Journal of interpersonal violence, 2021)
Using a sample of 1,190 married Spanish community couples in opposite-sex relationships, this study evaluated a path analytic model exploring the associations between individual and dyadic factors and partner aggression for both males and females. Specifically, the perpetrator’s report of their individual mental health symptomatology (borderline and antisocial traits, alcohol use), their report of relationship quality, and their report of perpetration were modeled to predict their partner’s victimization. The resultant model exhibited good fit as measured by multiple indices for both male-to-female and female-to-male perpetration. Furthermore, results demonstrated that antisocial and borderline traits were associated with each other, that alcohol use was associated with perpetration, and that one partner’s perpetration was associated with his or her partner’s victimization for both males and females. However, the pattern of significant pathways between individual pathology and relationship violence differed somewhat for male-to-female and female-to-male aggression. Given the results, policy makers concerned about prevention of partner aggression may consider interventions aimed at symptoms associated with antisocial and borderline traits and substance use, and may identify differential targets for intervention based on the perpetrator’s gender.